2019
DOI: 10.1002/asl.923
|View full text |Cite
|
Sign up to set email alerts
|

Separating and quantifying the distinct impacts of El Niño and sudden stratospheric warmings on North Atlantic and Eurasian wintertime climate

Abstract: Sudden stratospheric warmings (SSWs) significantly influence Eurasian wintertime climate. The El Niño phase of the El Niño-Southern Oscillation (ENSO) also affects climate in that region through tropospheric and stratospheric pathways, including increased SSW frequency. However, most SSWs are unrelated to El Niño, and their importance compared to other El Niño pathways remains to be quantified. We here contrast these two sources of variability using two 200-member ensembles of 1-year integrations of the Whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…The warm anomalies are centered over Southern Greenland and from the central Sahara northeastward across Saudi Arabia and Iran. These SAT impacts in WACCM are consistent with previous model‐based studies (e.g., Oehrlein et al., 2019). Composites of SAT anomalies following SPVs (Figures 6b and 6g) show largely similar patterns but of opposite sign as those following SSWs.…”
Section: Resultssupporting
confidence: 92%
“…The warm anomalies are centered over Southern Greenland and from the central Sahara northeastward across Saudi Arabia and Iran. These SAT impacts in WACCM are consistent with previous model‐based studies (e.g., Oehrlein et al., 2019). Composites of SAT anomalies following SPVs (Figures 6b and 6g) show largely similar patterns but of opposite sign as those following SSWs.…”
Section: Resultssupporting
confidence: 92%
“…The zonal wind anomaly at 60°N is also positive throughout the atmospheric column in AMIP, but not CESM‐LE, showing stronger stratosphere‐troposphere coupling in the AMIP runs that combine stratospheric and El Niño forcing. The mechanism for this is unclear, as previous work has suggested that El Niños are associated with negative AO and NAO indices, not positive ones (Oehrlein et al., 2019).…”
Section: Resultsmentioning
confidence: 92%
“…Oehrlein et al. (2019) showed that El Niños typically are associated with a negative mode of the NAO in the troposphere, but that is in the absence of strong stratospheric forcing. A tropospheric mechanism connecting equatorial Pacific warming and negative NAO‐like variability in the North Atlantic was also proposed by Mezzina et al.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship with the La Niña teleconnection is more obscure, and overall their implication during ENSO events is not clear, as other studies consider SSWs and ENSO as distinct sources of variability in the North Atlantic (e.g. Polvani et al 2017;Oehrlein et al 2019). Using the same set of sensitivity experiments as in the present study, Palmeiro et al (2021a) have concluded that while ENSO modifies the seasonal-mean state of the polar vortex by conditioning it to be more (less) easily perturbed during El Niño (La Niña), the actual triggering of SSWs (at higher-frequency time-scales) is largely unrelated to ENSO.…”
Section: Introductionmentioning
confidence: 94%